Trichoderma wuyiense (Hypocreales, Ascomycota), a new species from Wuyi Mountains, China - Ma, Yu-Kun; Yang, Shi-Jia; Li, Ye-Tong; Gao, Han-Xing; Li, Yu; Zhu, Zhao-Xiang (Phytotaxa, 2024)
We conducted an examination of Trichoderma collections from the Wuyi Mountains in Fujian province, China. Through a comprehensive analysis that combined morphological data, culture characteristics, and phylogenetic information based on rDNA sequences of the gene encoding the second largest nuc RNA polymerase subunit (RPB2) and the partial nuc translation elongation factor 1-α encoding gene (TEF1-α), we introduce a new species called Trichoderma wuyiense, along with its asexual morphological characteristics. Trichoderma wuyiense is characterized by trichoderma- to verticillium-like conidiophores, lageniform to subulate phialides, and globose to ellipsoidal conidia. Phylogenetic analyses revealed that T. wuyiense belongs to the Viride clade and is closely related to T. sparsum. We also discuss the distinguishing features that set the new species apart from its close relatives. This study contributes to the understanding of Trichoderma diversity in the Wuyi Mountains and provides valuable insights into the morphology, phylogeny, and taxonomy of Trichoderma species. The identification of T. wuyiense adds to our knowledge of fungal biodiversity and highlights the importance of considering both morphological and molecular characteristics for accurate species classification.